Process optimization of silver nanoparticle synthesis using response surface methodology - Chowdhury, Silvia; Sulaiman, Nadzril; Yusof, Faridah; Faruck, Mohammad Omer (Elsevier, 2016)
In recent decades, nanoparticles research has garnered a lot of interest, especially in finding more effective ways for their synthesis. This study aims to investigate the chemical mediated synthesis of silver nanoparticles (AgNPs) using silver salt and tri-sodium citrate as the reducing agent. Processing parameters were statistically optimized in order to produce high yield AgNPs and optimization were analyzed using Response Surface Methodology (RSM). Based on AgNPs yield production, analyzed using UV-vis spectrophotometer in the range of 350 to 420 nm, results show that out of the three parameters tested (AgNO3 and tri-sodium citrate concentrations and stirring time), all factors except stirring time contributed significantly to the production. Synthesized AgNPs at optimized condition (absorbance 0.9 AU at 420 nm wavelength) were then characterized using TEM and UV-vis analysis.